Experimental Investigation of Coherent Cherenkov Diffraction Radiation in Super-radiant Regime; Charged & Neutral Particles Channeling Phenomena – Channeling 2024 - Kubankin A. S. Aleksandr Sergeevich; Baldin A. A. Anton Aleksandrovich; Klenin A. A. Artemiy; Kidanova E. A. Ekaterina Alekseevna; Bushmina E. A. Elizaveta Alekseevna; Kishin I. A. Ivan; Nozdrin M. A. Mikhail; Karataev P. V. Pavel Vladimirovich; Stuchebrov S. G. Sergey Gennadevich; Alekseev S. V. Sergey; Kocharian (Kocharyan) V. R. Vagan Rashidovich; Margaryan V. Vardan; et al. (2024, 2024)
Recent years have witnessed an intense investigations of Cherenkov diffraction radiation (ChDR) appearing when a fast charged particle moves in the vicinity of and parallel to a dielectric interface. This is a member of polarization radiation family, because the radiation arises as a result of dynamic polarization of a medium. The ChDR properties are sensitive to various beam parameters including beam size, position, direction, beam energy, and bunch length. Coherent ChDR is generated in the wavelength range longer than or comparable to the longitudinal size of the bunch. In this case all electrons emit radiation more or less in phase stimulating each other’s emission. The radiation intensity is proportional to a square of bunch charge resulting in an enormous increase in the number of photons